Surveillance, Tyranny, and Technocratic Colonialism: A Critical Interrogation of Gen-AI Solutionism in Higher Education Curriculum - McInnes, Richard (Critical Education, 2026)
The adoption of generative artificial intelligence (gen-AI) in higher education curriculum design is often framed as an inevitable step toward efficiency and innovation. In this paper, I employ critical realism to interrogate the ideological and political dimensions of gen-AI adoption, arguing that it represents a form of technocratic colonialism that reinforces neoliberal and surveillance-driven imperatives. By interrogating who benefits from these technologies and whose interests are marginalised, I problematise gen-AI’s role in shaping knowledge production, academic labour, and epistemic hierarchies. Through a critical education lens, I highlight how universities, in their embrace of gen-AI, risk entrenching structures of control, eroding pedagogical autonomy, promoting epistemic dependence, marginalising educator expertise, and privileging dominant knowledge systems while excluding alternative epistemologies. Urging a shift from techno-solutionism to critical engagement, I advocate for resistance to gen-AI’s unchecked integration in curricula, ensuring that educational transformation remains grounded in equity, ethics, and intellectual agency.